Intermarriages – Crossing Political and Social Borders - Stojanova, Meri (Poznańskie Studia Slawistyczne, 2013)
This paper analyses Macedonian – Albanian intermarriages in Macedonia in the last fifteen years i.e. their frequency, routes and patterns set in correlation with the social and traditional relationship that existed and still exists in both „sending” and „receiving” communities. The foundation of such „new” constructions as Macedonian – Albanian intermarriages, deconstruct some of the already established norms both on the nuclear – family level and on the local – community level and reshape or construct new norms and relations within families and local communities as well.